2008
DOI: 10.1097/sap.0b013e3180d099fa
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Posterior Interosseous Flap in Childhood

Abstract: Restoration of complex hand defects in children is still problematic because of the limited choices of treatment. The reverse posterior interosseous flap is a versatile flap, with successful results shown in adults. The purpose of this study was to highlight the utility and versatility of the flap and to simplify the technique for ease of harvest in the pediatric age group. Complex hand defects were repaired using this flap in 10 children. Ages of the patients averaged 9.1 years. Fasciocutaneous and osteofasci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[25] Tan reported no flap necrosis in his PIO flap series comprising 10 children. [4] Büchler and Frey found partial flap necrosis in 21 percent of their series and ascribed this to arterial ischemia (71 percent) or venous congestion (29 percent). [24] Costa et al reported two patients with rim necrosis in 21 pedicled PIO flap transfers.…”
Section: Discussionmentioning
confidence: 97%
“…[25] Tan reported no flap necrosis in his PIO flap series comprising 10 children. [4] Büchler and Frey found partial flap necrosis in 21 percent of their series and ascribed this to arterial ischemia (71 percent) or venous congestion (29 percent). [24] Costa et al reported two patients with rim necrosis in 21 pedicled PIO flap transfers.…”
Section: Discussionmentioning
confidence: 97%